Factors that influence financial leverage on listed companies in bursa Malaysia / Ila Nabila Ali Badaruddin and Nurul Hidayah Ahmad Fauzi - Ali Badaruddin, Ila Nabila; Ahmad Fauzi, Nurul Hidayah (Faculty of Business Management, 2016)
The purpose of this study is to examine the factors of financial leverage that influence on listed companies in Bursa Malaysia from 1995 until 2014. Factors of leverage affected each company as it may bring harm to the company if it driven by bad influence. The level of influences itself will show the capabilities of every company whether they are in good condition or not. It is also important for them when they want to apply for loan or funds. Level of leverages are very importance since it is indicator for every company for them to go further as it will determine some decisions such as investment, and international business. If the financial leverage of company is too bad, this can affect the company in many aspects such as shareholder’s trust and also in financial industries if they want to make loans. This research is conducted due to researchers need to analyze the relationship of factors towards leverage that influences listed companies in Bursa Malaysia. Many factors were involved in this study, which are collateralized asset, profitability, and growth opportunity in Malaysia. In this study, researchers used construction, consumer, finance, plantation and trading service sectors that listed on Bursa Malaysia which are from year 1995 to 2014. The researcher found that the collateralized asset, profitability and growth opportunity on listed companies in Bursa Malaysia have a positive relationship with the financial leverage. Panel data consist of secondary data gathered Malaysia firm have been used for this study which employed Panel Regression Fixed Effect Model. Researcher use Econometric views 9 (E-Views 9) as medium to analyzed and interpret descriptive, normality and regression. Lastly, researchers have come out with the conclusion and recommendation about the research that can be done in the future.